Methods to generate site-specific conjugates of antibody and protein - Park, Jisoo; Lee, Sangwoo; Kim, Yuseon; Yoo, Tae Hyeon (Bioorganic and Medicinal Chemistry, 2021)
Antibody-protein conjugates have been useful tools for studying biological systems and also played important roles in developing therapeutics and diagnostics. In particular, because of the increased interest in therapeutics of complexity higher than monoclonal antibodies, various methods have been reported for generating bispecific antibodies, immunotoxins, and antibody-enzyme conjugates in which antibodies are site-specifically conjugated with other proteins. Compared with conjugating antibodies with synthetic molecules, controlling the modification sites is difficult in the antibodies conjugated with protein cargos due to the presence of several reactive groups in both molecules. Enzymatic reactions are often used to generate antibody-protein conjugates owing to their high specificity for both reactants and products. Chemical modifications involving genetic introduction of natural or unnatural amino acid residues have also been used for site-specific conjugation of antibodies. Recent studies have developed methods to modify native antibodies using peptides having affinity for antibodies, and these methods do not need antibody engineering for conjugation reactions. In this review, we have summarized enzymatic and chemical approaches to generate site-specific antibody-protein conjugates.
Keywords: Animals; Antibodies, Monoclonal; Humans; Proteins; Affinity peptide labeling; Antibody-protein conjugates; Bioorthogonal reactions; Enzymatic modification of antibodies; Site-specific conjugation